2019
DOI: 10.3390/app9071321
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Chitosan for the Generation of Functional Derivatives

Abstract: Today, chitosan (CS) is probably considered as a biofunctional polysaccharide with the most notable growth and potential for applications in various fields. The progress in chitin chemistry and the need to replace additives and non-natural polymers with functional natural-based polymers have opened many new opportunities for CS and its derivatives. Thanks to the specific reactive groups of CS and easy chemical modifications, a wide range of physico-chemical and biological properties can be obtained from this u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 240 publications
(337 reference statements)
1
95
0
1
Order By: Relevance
“…The authors suggested that TiO 2 may promote a modification of the CS-TiO 2 film matrix, forming a dense structure, which act as obstacles to water vapor diffusion through the film [28,50]. Similar trends were observed in the OVP properties through the incorporation of nano-TiO 2 to CS films according to Peng et al [59] and Lian et al [60], who stated that the presence of TiO 2 significantly improves the film functionality by reducing the exchange of oxygen through the CS-TiO 2 composite film [66]. Besides, no significant differences in water solubility were observed between CS and CS-TiO 2 films [57].…”
Section: Chitosan-tio 2 (Cs-tio 2 ) Compositesupporting
confidence: 52%
“…The authors suggested that TiO 2 may promote a modification of the CS-TiO 2 film matrix, forming a dense structure, which act as obstacles to water vapor diffusion through the film [28,50]. Similar trends were observed in the OVP properties through the incorporation of nano-TiO 2 to CS films according to Peng et al [59] and Lian et al [60], who stated that the presence of TiO 2 significantly improves the film functionality by reducing the exchange of oxygen through the CS-TiO 2 composite film [66]. Besides, no significant differences in water solubility were observed between CS and CS-TiO 2 films [57].…”
Section: Chitosan-tio 2 (Cs-tio 2 ) Compositesupporting
confidence: 52%
“…As described above, polysaccharides are abundantly present in lot of biomasses such as plant and microorganisms. If it is considered marine biotopes, seaweeds and crustaceans are the most important sources of polysaccharides [183,184]. Consequently, the last 2 decades lots of marine polysaccharides such as chitosan, alginate, agar-agar, and carrageenan have been largely described for their techno-functional applications.…”
Section: Marine Polysaccharidesmentioning
confidence: 99%
“…Several recent studies have shown that it is possible to use chitosan for food packaging, due to its physico-chemical properties [184]. In a very interesting review, Fernandez-Saiz [190] gave an overview of the food packaging applications using chitosan.…”
Section: Chitosanmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be used in the industry for making a suitable alternative for plastics. The chitin and its derivative polysaccharides are widely used for medical applications due to their biocompatibility and antimicrobial potency (Brasselet et al, 2019). It is fixed with a protein matrix of a crustacean shell.…”
Section: Introductionmentioning
confidence: 99%